2022
DOI: 10.22354/24223794.1105
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of ivermectin (400 ug/kg, single dose) in patients with severe COVID-19: a randomized clinical trial

Abstract: Purpose: To evaluate the clinical efficacy of including Ivermectin (single dose on day 1 of 400 ug/kg PO) in the standard of care in hospitalized adults with severe COVID-19. Methods: Double-blinded, parallel, placebo-controlled, single-center, randomized clinical trial. Seventy-five patients were randomly assigned (1:1) to receive standard of care plus ivermectin or placebo and were followed up for 21 days. Primary outcome measure was admission to ICU and secondary outcomes were the requirement of intensive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Characteristics of included studies are given in Table 1. Seventeen studies 47–63 were excluded as they were not RCTs and we identified 39 ongoing studies 64–102 and 2 studies 103,104 are awaiting classification.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of included studies are given in Table 1. Seventeen studies 47–63 were excluded as they were not RCTs and we identified 39 ongoing studies 64–102 and 2 studies 103,104 are awaiting classification.…”
Section: Resultsmentioning
confidence: 99%